Europese Raaklijnen : Hedendaagse Kunst uit de Lidstaten. - Benijts, Frank; Bettinger, S.-C.; Coessens, Piet; Coucke, Jo; Foncé, Jan; Hayes, Wim A.; Jooris, Roland; Lambrecht, Luk; Scheire, Octave; Van Buynder, Ernest; van Fleteren, H. (Deurle : Museum Dhondt-Dhaenens, 1989)
Baikas, Nicos ; Carr, Tom ; Cucchi, Enzo ; Fetting, Rainer ; Fitzgerald, Mary ; Fontaine, Jean de la ; De Keyser, Raoul ; Kirkeby, Per ; Lataster, Ger ; Leroy, Eugène ; Molin, Lei ; Mortier, Antoine ; Penck, A.R. ; Pistoletto, Michelangelo ; Raveel, Roger ; Sarmento, Julião ; Van Severen, Dan ; Tremlett, David
biog. per kunstenaar
Nederlands
Europese Raaklijnen : Hedendaagse Kunst uit de Lidstaten, Museum Dhondt-Dhaenens, Deurle, 22.04 - 28.05.1989
boek
Keywords: Europa